Rabbits, Rabbits, Rabbits: Show Rabbit Record Book - Joy C. Jordan; Loretta Rodriguez; Jessica Kochert; Bill Heltemes; Chris Decubellis; Renee Gore (EDIS)
When people discuss "Market Rabbits," they often think only of using rabbits for their meat. However, in this Florida 4-H project, youth have the opportunity to study not only meat rabbit production, but also the textile rabbit markets and pet or show stock production for their market project. In the 4-H Market Rabbit project (visit http://florida4h.org for more information about this online project), youth learn the skills necessary for choosing and maintaining healthy rabbit stock, proper handling of rabbits, rabbit health, and general care in addition to producing rabbits for a profit. This document, the Market Rabbit Record Book (4H RAR 13), familiarizes youth with the importance of record keeping as an integral part of project management. Records help youth keep track of vital information that can later help them make the best decisions regarding their animals. By tracking inventory, financial records associated with their project, rabbit health and growth details, industry-specific information such as wool/meat/kit yield, as well as pedigree/breeding and identification methods and dates, youth will be well prepared to relate their experiences in a written narrative as part of their project completion activities. Original publication date September 2010.